Evaluating several methods of JAK2 V617F mutation-genotyping to predict the risk of getting polycythemia vera and other myeloproliferative neoplasm diseases - Thy Ngoc, Nguyen; Bich Hau, Bui; Hoang Nam, Pham; Tuan Anh, Tran; Thi Trang, Do; Thi Xuan, Nguyen (Vietnam Journal of Biotechnology, 2021)
Polycythemia vera, essential thrombocythemia and primary myelofibrosis are members of the Philadelphia negative chronic subgroup of Myeloproliferative neoplasm. Published studies showed that the mutation JAK2 V617F is mostly responsible for the diseases; therefore, an accurate, low-cost and rapid molecular method to identify this mutation is important in screening and early diagnostic of these diseases. Different methods for genotyping of JAK2 V617F have been proposed. In this study, we evaluated the quality and cost-effectiveness of three genotyping methods, i.e., PCR-ARMS, PCR-RFLP, Sanger sequencing, to determine the appropriate genotyping for JAK2 V617F and predicted in silico the effect of this mutation on the structure and function of Janus kinase 2 protein. Results showed that the Sanger sequencing and PCR-RFLP genotyping methods were more accurate than PCR-ARMS. PCR-RFLP was also more rapid and economical than the other methods. In silico studies also demonstrated that the JAK2 V617F mutation had a large effect on the activity of corresponding protein. These results provided the initial data for further studies on genetic screening and prediction of myeloproliferative neoplasm and other related diseases in the Vietnamese population.